(untitled) - Fabozzi, Frank J. (London, 1998)
Foundations of Financial Markets and Institutions, offers a comprehensive exploration of the revolutionary developments occurring in the world's financial markets and institutions –i.e., innovation, globalization, and deregulation–with a focus on the actual practices of financial institutions, investors, and financial instruments.
Keywords: Finance,Financial institutions,Tài chính,Cơ quan tài chính